2001
DOI: 10.1080/089106001750071717
|View full text |Cite
|
Sign up to set email alerts
|

Survival ofSerratia marcescensin the Presence of Complement

Abstract: Serratia marcescens has been isolated from a variety of ocular infections and:or in ammation. In order to survive in the eye, strains must be able to resist host defence systems. Complement has been shown to have an increased concentration and to be active during sleep. Not only is the complement system involved in host defence, but its activation can also produce in ammation. The aim of the present study was to examine the ability of ocular isolates of S. marcescens to withstand complement attack, activate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…When the strains were opsonized, both SVH and Smar 2 were sensitive to phagocytosis by PMNs. These two strains also were sensitive to complement attack, 12 which suggests a common mechanism for the serum-resistant strains in both assays. The activation of the respiratory burst and the resistance to phagocytic killing by PMNs may contribute to corneal destruction and inflammation in MK or further inflammation in adverse responses such as CLARE.…”
Section: Discussionmentioning
confidence: 95%
“…When the strains were opsonized, both SVH and Smar 2 were sensitive to phagocytosis by PMNs. These two strains also were sensitive to complement attack, 12 which suggests a common mechanism for the serum-resistant strains in both assays. The activation of the respiratory burst and the resistance to phagocytic killing by PMNs may contribute to corneal destruction and inflammation in MK or further inflammation in adverse responses such as CLARE.…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that S. marcescens can grow in the presence of lysozyme and lactoferrin 8 as well as complement. 9 However, it is unknown how these bacteria are able to initiate infection or inflammation. Bacteria are known to induce cytokines that may enhance polymorphonuclear leukocyte (PMN) infiltration into the cornea.…”
mentioning
confidence: 99%